National Park Mljet - Place of Conflicting Interpretations - Šantek, Goran Pavel (2012)
National parks are complex phenomena of heritage production and protection, but at the same time a place of often conflicting interpretations of the manner of their establishment, regulation, and the use of their natural and cultural resources. This concerns at least two rypes of players: local inhabitants and the representatives of the Park or State.